Spatially explicit paleoclimate reconstruction of South America for the last 800 thousand years - Thiago F Rangel; Neil R Edwards; Philip B Holden; José Alexandre F Diniz-Filho; William D Gosling; Marco Túlio P Coelho; Fernanda A S Cassemiro; Carsten Rahbek; Robert K Colwell (PANGAEA, 2018)
For each 500-year time interval from 800 Ka (years ago) to the present (1600 time steps), we used a paleoclimate model to assign to each of the 4820 map cells an estimate of the mean temperature of the warmest and coolest quarters and the mean daily precipitation of the wettest and driest quarters. These four factors, on two environmental axes (annual temperature and annual precipitation) characterize the changing climate in each grid cell over the time-course of the simulation. The database consists of the paleoclimate data used in this simulation. It is composed of one text file for each climate variable: (1) minimum annual precipitation, (2) maximum annual precipitation, (3) minimum annual temperature, and (4) maximum annual temperature. Within each file, each row represents a single map cell (4820 in total). The first two columns are the geographical coordinates of each grid cell (latitude and longitude in decimal degrees). The succeeding columns describe the climate variable at each time slice of the series, at successive 500-year intervals. Each column is labeled Tx, where x is thousands of years before present. For example, column “T795.5” of file “PrecipAvgAnnualMax.txt” contains the map cell data for maximum annual precipitation at 795.5kya.
Supplement to: Rangel, TF et al. (2018): Modeling the ecology and evolution of biodiversity: Biogeographical cradles, museums, and graves. Science, 361(6399), eaar5452, https://doi.org/10.1126/science.aar5452